On Linear Relations Generated by Nonnegative Operator Function and Degenerate Elliptic Differential-Operator Expression - Bruk, V. M. (Журнал математичної фізики, аналізу, геометрії, 2009)
In terms of boundary values, we describe a spectrum of the linear relations indicated in the paper title. We study the invertible restrictions of maximal relation and show that the operators inverse to these restrictions are integral. The criterion of holomorphicity of the family of these operators is determined. Using the results obtained, we show that the minimal relation is symmetric in Hilbert space and describe all generalized resolvents of this relation.Mathematics Subject Classification: 47A06, 47A10, 34B05.